Additional changes to taxonomy ratified in a special vote by the International Committee on Taxonomy of Viruses (October 2018) - Siddell, Stuart G.; Walker, Peter J.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adams, Michael J.; Dutilh, Bas E.; Gorbalenya, Alexander E.; Harrach, Balázs; Harrison, Robert L.; Junglen, Sandra; Knowles, Nick J.; Kropinski, Andrew M.; et al. (Archives of virology, 2019)
This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in October 2018. Of note, the ICTV has approved, by an absolute majority, the creation of additional taxonomical ranks above those recognized previously. A total of 15 ranks (realm, subrealm, kingdom, subkingdom, phylum, subphylum, class, subclass, order, suborder, family, subfamily, genus, subgenus, and species) are now available to encompass the entire spectrum of virus diversity. Classification at ranks above genus is not obligatory but can be used by the authors of new taxonomic proposals when scientific justification is provided.